Students’ English Language Learning Strategy and Implication to the Teaching and Learning Activity: A Study at Health Vocational Schools (SMK Kesehatan) in Ruteng at Flores - Daar, Gabriel Fredi (International Journal for Educational and Vocational Studies, 2019)
Different theorists proposed different definition of learning strategies (Wenden, 1987, O’Malley and Chamot, 1990, Oxford, 1990).  All the definitions highlighted that learning strategies are the actions taken to make learning easier, faster, more enjoyable, more self-directed, more effective, and more transferrable. The study aims to find out how Health Vocational School students in Ruteng, Flores employ learning strategies, what strategy is mostly employed and the implications of learning strategy employed to language learning and teaching which cover cognitive strategy, meta cognitive strategy and social strategy. It’s mixed method research combining the use of quantitative and qualitative study.  For the purpose of quantitative study, it was chosen 123 students by using the technique of cluster random sampling, meanwhile for the purpose of qualitative data, it was chosen 12 students and three English teachers by using purposive sampling. The research result shows that students of health vocational schools in Ruteng, Flores employ medium language learning strategy for the three learning strategies studied (Cognitive strategy employed by 90,2% (111) students, meta cognitive strategy employed by 86,2%(106) students, and social strategy employed by 86,2% (106) students. Regarding learning strategy mostly employed, the most frequent strategy is cognitive strategy which gains the mean 3.33. Meanwhile, the least strategy is social strategy and it reaches the mean of 3.26.  Medium learning strategy for the three strategies studied, and cognitive strategy as the most frequent strategy employed has the implication to applying teaching method which is oriented to raise up students’ cognitive strategy, adopting regularly the meta cognitive instruction in the classroom to help students improve academic achievement, and providing the opportunity for students to practice speaking English out of the classroom.